CONTRIBUTION TO USAGE PRESENTATIONS IN TEACHING PROCESS - Milan, BROZ (Trends in education, 2010)
The article deals with using and making presentations in the teaching process. Highlights some important aspects of creating presentations. As an example, mentioned the use of presentations to the Commercial College in Prague (VSO in Prague).
Keywords: presentations; slides; layouts; shapes; inserting objects; PowerPoint.